CEO Activism and the Backfire Effect: Lessons from Erspo’s Reputational Crisis and the Mechanics of Digital Spillover - Rani amartha Aurelia; Irvani Saputri; Naswa aulia Rahmawati; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
The digital landscape of 2026 has witnessed a fundamental transformation in public relations, where the Chief Executive Officer (CEO) serves as a symbolic manifestation of corporate identity. This conceptual article examines the